Penciptaan Souvenir Jam Dinding Ornamen Karo Berbahan Dasar Kayu dengan Teknik Ukir - Jimmi Micael Ginting; Misgiya Misgiya (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2025)
This study presents a woodcraft creation in the form of a wall clock with traditional Karo ornaments as the main visual element. The creation is driven by the urgency to preserve the visual culture of the Karo people, which is increasingly threatened by modernization, and the lack of distinctive local souvenirs in tourist areas such as Berastagi, which often offer only generic or mass-produced items. This creation aims not only to function as an indicator of time but also as a medium for cultural preservation, education, and the strengthening of the Karo visual identity in a contemporary context. The creative process applies the "three stages and six steps" approach by S.P. Gustami, which includes exploration, design, and realization. Exploration involves field observations of Karo architecture and artifacts, literary studies on Karo visual symbols, and careful selection of motifs, focusing on Tapak Raja Sulaiman, Takal Kerbo, and Pengeret-ret as representative elements rich in symbolic meaning. The design stage produces various sketches that integrate the functional aspect of the wall clock with the principles of ornamentation, ensuring both utility and cultural expression. Realization involves selecting local woods such as teak, mahogany, and jelutung, followed by manual carving techniques, the application of natural wood coloring, and protective finishing with melamine spray to ensure durability and aesthetic quality. The final result consists of twelve unique wall clocks that embody the aesthetic, symbolic, and cultural richness of the Karo people. This work demonstrates how traditional motifs can be re-contextualized into functional objects, making cultural heritage more visible and relevant in daily life, and is expected to inspire further innovation in the local crafts industry, contributing to long-term preservation and revitalization of regional cultural identity.